Green Biodiesel Synthesis Using Waste Shells as Sustainable Catalysts with Camelina sativa Oil - Yelda Hangun-Balkir (Journal of Chemistry)
Waste utilization is an essential component of sustainable development and waste shells are rarely used to generate practical products and processes. Most waste shells are CaCO3 rich, which are converted to CaO once calcined and can be employed as inexpensive and green catalysts for the synthesis of biodiesel. Herein, we utilized lobster and eggshells as green catalysts for the transesterification of Camelina sativa oil as feedstock into biodiesel. Camelina sativa oil is an appealing crop option as feedstock for biodiesel production because it has high tolerance of cold weather, drought, and low-quality soils and contains approximately 40% oil content. The catalysts from waste shells were characterized by X-ray powder diffraction, Fourier Transform Infrared Spectroscopy, and Scanning Electron Microscope. The product, biodiesel, was studied by 1H NMR and FTIR spectroscopy. The effects of methanol to oil ratio, reaction time, reaction temperature, and catalyst concentration were investigated. Optimum biodiesel yields were attained at a 12 : 1 (alcohol : oil) molar ratio with 1 wt.% heterogeneous catalysts in 3 hours at 65°C. The experimental results exhibited a first-order kinetics and rate constants and activation energy were calculated for the transesterification reaction at different temperatures. The fuel properties of the biodiesel produced from Camelina sativa oil and waste shells were compared with those of the petroleum-based diesel by using American Society for Testing and Materials (ASTM) standards.